The Crystallographic Groups and Weakly Amenable groups - Kannan, K. (International Journal of Mathematical Analysis, 2014)
The purpose of this paper is to provide an illustration of an interest ing and nontrivial interaction between analytic and geometric properties of a group. We prove that the Crystallographic groups need not be weak amenable.
Keywords: Weakly amenable; Invariant Approximation property; Discrete Heisenberg Group